Electrochemical Sensors and Biosensors of Biomarkers and Therapeutic Agents Detection - Abdelhakem, Mahmoud (AUC Knowledge Fountain, 2023)
Electrochemical sensing is a pioneering tool amongst all other sensing techniques even though it had been started in the early 20th century. Due to their cost efficacy, accuracy, and real-time measurement, electrochemical sensing has been utilized in a vast of biomedical applications in therapeutic drug monitoring and biomarker detection. This thesis work concerned the monitoring of three therapeutic agents in spiked plasma, urine, dosage form, and interstitial skin fluid with high specificity and accuracy. Two of our sensing platforms utilized nanomaterials for sensing (sensors) of Cilostazol and Velpatasvir utilizing α-MnO2-V2O5 (metal oxide nanorods) and NH2- MIL-53 (Aluminum-based metal organic frameworks), respectively. Nanomaterial-based sensors are optimal for electrochemically active therapeutic agents due to their cost-effectiveness and nonlaborious preparation, which was the case for Cilostazol and Velpatasvir. However, for vancomycin that is electrochemically inactive and has very high priority to be monitored due to its efficacy against methicillin-resistant Staphylococcus Aureus and its high toxicity, an advanced level of biosensor was utilized for its detection that is minimally invasive. Aptamers have been utilized due to their low cost of preparation compared to other biorecognition molecules, and their capability to generate signal upon binding to the target molecule that is associated to the attached methylene blue to its 3’ end. All of our sensors possessed a wide range of linearity, high reproducibility, high sensitivity, and low limit of detection.